¿Cárcel para colusores? Reflexiones sobre la criminalización de las prácticas anticompetitivas en el Perú - Floríndez Aramburú, Francisco José (2020)
On August 29, 2020, in an attempt to address some of the public's claims in the context of the health crisis, the Congress of the Republic of Peru approved Law 31040, a Law amending the Criminal Code and the Consumer Protection Code, with regard to hoarding, speculation and adulteration, which aims to criminalize the execution of anticompetitive practices. Thus, these practices, until before the enactment, merited only administrative sanctions imposed by Indecopi's Committee on the Defense of Free Competition.In this paper, the authors present some reflections on the compatibility of that Act with the Peruvian legal system. In this way, they substantiate why it constitutes an obstacle to the suppression of anticompetitive practices and increases the level of legal uncertainty for potential offenders.